Writing the ancestral river : a biography of the Kowie - Cock, Jacklyn (Book collections on Project MUSE., 2018)
Writing the Ancestral River is an illuminating and unusual biography of the Kowie River in the Eastern Cape. This tidal river runs through the centre of what used to be called the Zuurveld, a formative meeting ground of different peoples who have shaped South Africa's history: Khoikhoi herders, Xhosa pastoralists, Dutch trekboers and British settlers. Their direct descendants continue to live in the area and interact in ways that have been decisively shaped by their shared history. Besides being a social history, this is also a natural history of the river and its catchment area, where dinosaurs once roamed and cycads still grow. As the book shows, the natural world of the Kowie has felt the effects of human settlement, most strikingly through the establishment of a harbour at the mouth of the river in the 19th century and the development of a marina in the late 20th century. Both projects have had a decisive and deleterious impact on the Kowie. By focusing on this 'little' river, the book raises larger questions about colonialism, capitalism, 'development' and ecology. In particular, it asks us to consider the connections between social and environmental justice and injustice. As the author says, 'around the world people are increasingly reconnecting with nature and justice through rivers. Unlike other bodies of water, such as dams, oceans and lakes, rivers have a destination and we can learn from the strength and certainty with which they travel. I believe this learning is valuable because acknowledging the past, and the inter-generational, racialised privileges, damages and denials it established and perpetuates, is necessary for any shared future'.